Accumulation of advanced glycation end products evaluated by skin autofluorescence and incident frailty in older adults from the Bordeaux Three-City cohort - Pilleron, Sophie; Rajaobelina, Kalina; Tabue Teguo, Maturin; Dartigues, Jean-François; Helmer, Catherine; Delcourt, Cécile; Rigalleau, Vincent; Féart, Catherine (PloS one, 2017)
We analyzed the cross-sectional and prospective relationships between the accumulation of advanced glycation end products (AGE), assessed by skin autofluorescence (AF) and frailty and its components. A total of 423 participants of the Bordeaux sample of the Three-City study 75 years of age or older in 2009-2010 were included in the cross-sectional analysis. Among them, 255 initially non-frail participants were re-examined 4 years later. Skin AF (arbitrary units (AU)) was measured using the AGE Reader. Frailty was defined using Fried's criteria. Associations were assessed with logistic regression models. Mean skin AF at baseline was 2.81 ±0.68 AU and 16.8% participants were frail. Adjusted for sociodemographic and health characteristics, skin AF was associated neither with prevalent frailty as a whole (Odds Ratio (OR) = 1.2; 95% Confidence Interval: 0.8-1.9) nor with any of its components. Among 255 non-frail participants, 32 became frail over 4 years. In multivariate analyses, skin AF was not associated with incident frailty as a whole (OR = 1.0; 0.5-2.0) but with a doubled risk of incident exhaustion (OR = 2.0; 1.2-3.6) and low energy expenditure (OR = 2.0; 1.1-3.7). No association was observed with other criteria. In French older community-dwellers aged 75 years and over, the accumulation of AGEs evaluated by skin AF was not associated with prevalent or incident frailty but with the 4-year risk of exhaustion and low energy expenditure. Further studies with larger samples are needed to confirm our results.